Halal Trip Scheme: Implementation of Shariah Compliance in Indonesia - Riska Sayidah; Zahra Fitria; Sintia Nurul Fuadah; Rizal Faozi; Jaenudin Jaenudin; Agi Attaubah Hidayat (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to analyze the implementation of the halal travel scheme in Indonesia and evaluate its compliance with sharia economic law, particularly focusing on standards set by DSN-MUI Fatwa No. 108/2016. Method: Using normative legal methods through a study of relevant legal regulations and literature, especially DSN-MUI Fatwa No. 108/2016. The study focuses on key sharia principles and assesses their application within the halal trip scheme, especially through innovations like the "Halal Tripnesian" platform. Result: The findings demonstrate that Indonesia's halal trip scheme largely aligns with sharia compliance standards, effectively incorporating critical elements such as halal-certified food, prayer facilities, and sharia-compliant accommodations. Despite facing challenges, including diverse interpretations of sharia law, a lack of unified global halal certification, and varying levels of halal literacy among stakeholders, the overall implementation has shown strong adherence to sharia principles. Technological innovations, particularly through digital platforms, have enhanced the accessibility and convenience of halal travel, supporting the growth of the sector and positioning Indonesia as a leading destination for Muslim-friendly tourism. Contribution: This study provides insights into the strengths and weaknesses of Indonesia’s halal travel scheme, highlighting the importance of regulatory support, digital innovation, and stakeholder education in ensuring sharia compliance. The research suggests that continued efforts in harmonizing halal standards and improving halal literacy are essential for sustaining growth and competitiveness in the global halal tourism market.